Association between social participation and hope levels in stroke patients: a cross-sectional study - Liu, Miao; Liu, Yan; Li, Tian; Yang, Jiying; Wang, Juan; Wang, Hen (Frontiers in Psychology, 2025)
ObjectivesExploring Factors Influencing the Level of Hope in Stroke Patients and Its Relationship with Social Participation.MethodsWe conducted a cross-sectional study at Wuhan University People’s Hospital from March to June 2024 and performed a correlation analysis on the sample data. Using convenience sampling, we enrolled 122 stroke patients who met the inclusion criteria. Participants completed questionnaires assessing social participation (Impact on Participation and Autonomy Questionnaire, IPA), hope (Herth Hope Index, HHI), activities of daily living (Barthel Index), and sociodemographic/disease characteristics. Data were analyzed using SPSS 26.0 with descriptive statistics, t-tests, ANOVA, Pearson correlation, and multiple linear regression. All statistical tests were two-tailed with significance set at p < 0.05. Effect sizes were reported with 95% confidence intervals.ResultsParticipants demonstrated moderate social participation impairment (IPA: 32.60 ± 16.32), with the most pronounced limitations in autonomous participation in family roles (subscore: 11.10 ± 6.17). Hope levels averaged within the moderate range (HHI: 30.81 ± 7.28). Furthermore, significant negative correlations existed between all dimensions of social participation and all dimensions of hope (p < 0.01). Regression analysis indicated that Barthel Index and social participation were key factors influencing hope levels among stroke patients.ConclusionThis study demonstrates that stroke survivors exhibit moderate impairments in social participation and hope levels. These findings suggest that rehabilitation programs should prioritize social participation enhancement while providing targeted interventions for female patients and those with lower socioeconomic status or poorer functional ability. Further longitudinal research is needed to establish causal relationships and optimize intervention strategies.